M13 Bacteriophage Biolaminates for Nanomaterials with Improved Stiffness. Issue 1722 (16th June 2015) - Warner, Christopher M.; Ghoshal, Amitabh; Cuddy, Michael F.; Poda, Aimee R.; Barker, Natalie D.; Morse, Daniel E.; Lee, Seung-Wuk; Perkins, Edward J.
ABSTRACT: In nature, biomolecules guide the formation of hierarchically-ordered, lightweight, inorganic-organic composites such as corals, shells, teeth and bones. M13 bacteriophage has been used to mimic bio-inspired material development due to its rigid, nanoscale rod-like morphology. Liquid-crystalline monolayers of genetically engineered phage have been used to template crystallization of thin layers of inorganic and metallic materials. We have created thin films composed of engineered M13 phage capable of binding inorganic components. We employed both a dip-cast and a drop-cast film fabrication method on both smooth and rough gold, silica and glass casting surfaces to create thin films and 3D structures of various degrees of hierarchical order. We have found the engineered M13 phage and the inorganic mineral significantly affected both film morphology and the mechanical properties of the film. Similarly, film fabrication parameters such as solution chemistry, temperature, and pulling speed affected film properties. Using a calcium phosphate biomineralized 4E phage, film thickness increased linearly with the number of layers/dips in the phage solution. The stiffness of these composites (Young's modulus) were >80 GPa for mineralized, multilayer films. These materials are an order of magnitude stiffer than the biological equivalent collagen. Stiffness, however, does not appear to increase in a multilayer film beyond a saturation point. Ultimately, we have developed a platform for phage-based bio-composites for developing high performance materials.